2007
DOI: 10.1111/j.1365-2672.2006.03104.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Escherichia coli O157:H7 in the rhizosphere of maize grown in waste-amended soil

Abstract: Aims:  To assess whether the persistence of Escherichia coli O157:H7 in soil amended with cattle slurry and ovine stomach content waste is affected by the presence of a maize rhizosphere. Methods and Results:  Cattle slurry and ovine stomach content waste were inoculated with E. coli O157:H7. Wastes were then applied to soil cores with and without established maize plants. The pathogen survived in soil for over 5 weeks, although at significantly greater numbers in soil receiving stomach content waste in compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 41 publications
2
18
0
1
Order By: Relevance
“…Soil organic carbon also helps to improve soil structure by forming multi-pored aggregates which serves as microbial habitats [49]. Therefore, the abundance of organic carbon in soil can provide more nutrients, water, air and biological niches for E. coli O157:H7 and decrease the competition with indigenous microorganisms, slowing the decline of E. coli O157:H7 [3], [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil organic carbon also helps to improve soil structure by forming multi-pored aggregates which serves as microbial habitats [49]. Therefore, the abundance of organic carbon in soil can provide more nutrients, water, air and biological niches for E. coli O157:H7 and decrease the competition with indigenous microorganisms, slowing the decline of E. coli O157:H7 [3], [15].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Escherichia coli O157:H7 ( E . coli O157:H7), which can cause severe hemorrhagic colitis and haemolytic uraemia in humans, can persist in soil for days to more than 1 year following manure application to land [3]. It was reported that 20 people were infected with E .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that intensity of land-use (Jangid et al, 2008), length of time under a particular management (Buckley and Schmidt, 2001), substrate addition (Degens et al, 2000) and the presence of a plant rhizosphere (Garbeva et al, 2004) can contribute to defining microbial community structure. Some work has been carried out to demonstrate the effects of land-use and management on pathogen suppression (van Elsas et al, 2002;Williams et al, 2007;Franz et al, 2008;Yao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…were found in higher numbers in barley (Hordeum vulgare) rhizosphere soil, but the bacteria did not colonize root tissue [35]. Escherichia coli O157:H7 survived in soil for 35 days, but growth and survival were not different between bulk and rhizosphere soils [36]. The growth and survival of enteric bacteria in rhizosphere soils necessarily compete for resources including carbon sources, amino acids, nutrients, and moisture with the soil microbial community in that rhizosphere.…”
Section: Discussionmentioning
confidence: 99%